Short stature as a significant marker in celiac disease - Bohra, Jasraj; Gupta, Virendra K.; Gupta, Ashok (International Journal of Contemporary Pediatrics, 2019)
Background: Celiac disease (CD) is a genetically determined gluten-sensitive enteropathy resulting in nutrient malabsorption, can have extra gastrointestinal tract (GIT) presentations, short stature may be the only presenting clinical feature, even in the absence of gastrointestinal symptoms. The aim and objective of this study was to Methods: This cross-sectional study was performed on 1000 children between ages 5 to 10 year of different schools, in Jaipur, district of Rajasthan. An anthropometric measurement (height, weight) was done for all children. Serum samples were analyze for IgA antibodies to human tissue transglutaminase (tTG) with lower detection limit of 1.0 U/ml and 15 U/ml. Positive samples for tTG antibodies were reanalyzed human endomysial autoantigens (EmA). Results: Out 1000 children screened, six were seropositive, of those four were females and two were males. The serological proportion of CD in this population was 1:166. These Six seropositive group tends to have lower height, weight than the seronegative group, but the difference was only significant for height (P=<0.01). Conclusions: Although gastrointestinal manifestations are important presentation of celiac disease, nevertheless short stature alone or in combination with other symptoms of celiac disease has been present.